Human interface and the management of information. Information and interaction design : 15th International Conference, HCI International 2013, Las Vegas, NV, USA, July 21-26, 2013, Proceedings, Part I - Yamamoto, Sakae (Lecture Notes in Computer Science,, 2013)
The three-volume set LNCS 8016, 8017, and 8018 constitutes the refereed proceedings of the 15th International Conference on Human-Computer Interaction, HCII 2013, held in Las Vegas, NV, USA in July 2013. The total of 1666 papers and 303 posters presented at the HCII 2013 conferences was carefully reviewed and selected from 5210 submissions. These papers address the latest research and development efforts and highlight the human aspects of design and use of computing systems. The papers accepted for presentation thoroughly cover the entire field of human-computer Interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas. This volume contains papers in the thematic area of human interface and the management of Information, addressing the following major topics: interacting with information, information searching, browsing and structuring, design and development methods and tools for interactive systems and services, personalized information and interaction, cognitive and emotional aspects of interacting with information.